Evaluation of Online Admissions Information System Utilizing the Technology Acceptance Model - Lian, Chuan De; Yuzhak, Nauval Dwi (International Journal of Informatics and Information Systems, 2024)
Admission of New Students covers the entire process, from registration and administrative selection to graduation announcement. This activity is an annual routine that is the first step in finding quality prospective students. Therefore, there is a need for a valuable and user-friendly online PMB website. Based on these problems, it is necessary to assess the success of implementing the PMB Online system at Amikom Purwokerto University using the Technology Acceptance Model (TAM) approach. This system development method refers to TAM, which emphasizes user perceptions of two main variables: usefulness and ease of use. Variables that describe user acceptance of the PMB Online system include Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, Attitude Towards Using, and Intention to Use. The results of this study indicate that Perceived Ease of Use has a positive effect on Perceived Usefulness, and Perceived Usefulness has a positive effect on Attitude Towards Using and Intention to Use. Meanwhile, Perceived Enjoyment also has a positive effect on Attitude Towards Using. The results of this study are expected to identify weaknesses and improve certain aspects to optimize the implementation of PMB Online at Amikom Purwokerto University.